Simultaneous incorporation of magnesium and fluorine ions in hydroxyapatite coatings on Ti6Al4V implant. - Cai, Yanli. (2011)
Hydroxyapatite (HA) coated titanium alloys are available as hard tissue implant material. However, the performance is not satisfactory due to insufficient short-term osseointegration and long-term stability of the implant. Studies show that cation incorporation (Mg) into HA resulted in better biological performances, i.e. short-term osseointegration, and anion incorporation (F) into HA decreased the dissolution rate and improved the adhesion strength, i.e. long-term stability. As such, a combination of good short-term osseointegration and long-term stability of the implant is achieved by properly incorporating both cation and anion into HA. This project aims at developing a bi-layer structured Mg and F ions co-substituted HA coating on Ti6Al4V substrate to achieve an integration of short-term osseointegration and long-term stability. Ca10-xMgx(PO4)6F1(OH)1 or MgxFHA in short, Ca9Mg1(PO4)6Fy(OH)(2-y) or MgFyHA in short, and the bi-layer structured HA (BHA in brief) coatings are deposited by a sol-gel dip-coating method. The compositional dependence of co-substitution of Mg and F ions is systematically studied on material structure, in vitro bioactivity, cell response, dissolution rate, and adhesion strength. The results show that as-deposited MgxFHA coatings have a single FHA phase when x ≤ 1.0. A small amount of Mg-substituted β-tricalcium phosphate (β-TCMP) appears together with FHA phase when 1.0 < x ≤ 2.0. The phases of as-deposited MgFyHA coatings depend on F concentration. Without F incorporation, β-TCMP is the main phase, and HA as the secondary phase. When y is 0.5, HA becomes the main phase and only a little β-TCMP presents. Single FHA phase forms when y ≥ 1.0. Grazing incidence X-ray diffraction, X-ray photoelectron spectroscopy, fourier transform infra-red spectroscopy results indicate that Ca ions and OH groups in HA crystal structure are substituted with Mg and F ions, respectively. High Mg concentrations (1.0 ≤ x ≤ 2.0) in the MgxFHA coatings improve the in vitro bioactivity a lot. However, F concentration does not influence the bioactivity of the MgFyHA coatings. MG63 cells attach and spread well on all the MgxFHA and MgFyHA coatings. In the MgxFHA coatings, Mg ions show a significant stimulating effect on cell proliferation and late cell differentiation when x is 1.5. F concentration studied does not affect cell numbers grown on the MgFyHA coatings. However, it maintains a positive stimulating on cell differentiation. The incorporation of Mg increases the dissolution rate of MgxFHA coating in the tris-buffered saline (TBS) solution, and the maximum is achieved at x = 1.5. F incorporation decreases the dissolution rate of MgFyHA coating in the TBS solution, especially at the measured fluoridation degree of 0.72 – 1.16. Mg substitution enhances the adhesion strength, but comparable among different Mg concentrations. Greatly enhanced adhesion strength is achieved by F incorporation at the measured F concentration around 1.0. Finally, Mg1.5FHA/MgF1.5HA bi-layer structured HA coating is developed. Single FHA phase forms in the coating with the substitution of Mg and F ions in HA lattice. It shows comparable in vitro bioactivity with pure HA coating, but more significant cell proliferation. The long-term stability of the bi-layer structured HA coating is much better than pure HA coating, exhibiting lower dissolution rate and higher adhesion strength.